PENGARUH PENGELUARAN KONSUMSI RUMAH TANGGA TERHADAP PRODUK DOMESTIK BRUTO INDONESIA TAHUN 2017-2018 - Wijayanti, Rahayu (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2023)
Gross Domestic Product  (GDP) is one of the economics growth benchmarks in a country. Gross Domestic Product (GDP) affected by several components. One component that affects GDP regarding expenditure is the Household Consumption Expenditure Component. This study is descriptive based. The data in this study are secondary data that is published by Indonesian Central Bureau odf Statistics (BPS) in 2017 to 2018. The result of this study shows that : (1) Household Consumption Expenditure not significant effect on rate of Indonesian Gross Domestic Product growth in 2017-2018; (2) Household Consumption Expenditure significantly affected structure of Indonesia’s Gross Domestic Product growth in 2017-2018.